Study of Test Anxiety of Freshmen Engineering Boys and Girls Students and their Academic Performance in Science & Humanities Subjects - Reddy, P Bhaskara; Reddy, R Praveen; Reddy, M Kantha (Transactions on Engineering and Computing Sciences, 2016)
the main aim of this learning was the effect of teaching of self-regulation on test anxiety; college achievement and met cognition in boy students, The Society under study include all boy and girl students of MLRIT. From this society 154 persons were randomly selected as sample that include experiment and control groups and 110 persons were selected for comparative analyzes. Measurement tools was Test-anxiety inventory that encountered of reliability and validity. Plan of research was kind of pre-test and post-test with manage group. After of pre-test, experimental groups four week, every week, two sessions and every session, , an hour to share in education class of self-regulation. After of end experimental to accomplish post test with two groups. The results of T-test show that there are significant difference between test anxiety in pre-test and post-test. Also we can see differenced levels of test anxiety between this student (22.4=low, 56.8=medium 18.4=high, 18.6 tremendous). Mean scores of test anxiety among students whose parents have academic education is higher than whom their parents don’t have academic education that show parents with academic education have more stringent whereas, results of t-test show that there are no significant differences between parents with academic education and no academic education also There are no significant different in mother profession and there are significant difference between boys and girls test anxiety (t=-4.76, p<0.00). With comparison Mean of two groups discover that girls encounter higher test anxiety. Results of meta cognition analyzes show that Mean scores in post-test are higher than pre-test however analyze with t-test method show that there are not significant difference between experimental and control groups in post-test of global reading, problem-solving, support research strategies and total score. results of academic achievement analyzes show that mean scores of courses increase in post-test that show self-regulation is useful in practicable and reading courses. With comparison Mean scores in foreign language books discover that pre-test are almost similar to post-test. Besides analyze with t-test methods show that there are significant difference between experimental and control groups in English, physics, chemistry and mathematics courses (p<0.05) however there are no significant difference in mathematical methods, drawing, English and Hindi courses.